BDNF Val66Met Genetic Polymorphism Results in Poor Recovery Following Repeated Mild Traumatic Brain Injury in a Mouse Model and Treatment With AAV-BDNF Improves Outcomes - Giarratana, Anna O.; Teng, Shavonne; Reddi, Sahithi; Zheng, Cynthia; Adler, Derek; Thakker-Varia, Smita; Alder, Janet (Frontiers in Neurology, 2019)
Clinicians have long noticed that some Traumatic Brain Injury (TBI) patients have worse symptoms and take a longer time to recover than others, for reasons unexplained by known factors. Identifying what makes some individuals more susceptible is critical to understanding the underlying mechanisms through which TBI causes deleterious effects. We have sought to determine the effect of a single nucleotide polymorphism (SNP) in Brain-derived neurotrophic factor (BDNF) at amino acid 66 (rs6265) on recovery after TBI. There is controversy from human studies as to whether the BDNF Val66Val or Val66Met allele is the risk factor for worse outcomes after brain trauma. We therefore investigated cellular and behavioral outcomes in genetically engineered mice following repeated mild TBI (rmTBI) using a lateral fluid percussion injury model. We found that relative to injured Val66Val carriers, injured Val66Met carriers had a larger inflammation volume and increased levels of neurodegeneration, apoptosis, p-tau, activated microglia, and gliosis in the cortex and/or hippocampus at 1 and/or 21 days post-injury (DPI). We therefore concluded that the Val66Met genetic polymorphism is a risk factor for poor outcomes after rmTBI. In order to determine the mechanism for these differences, we investigated levels of the apoptotic-inducing pro BDNF and survival-inducing mature BDNF isoforms and found that Met carriers had less total BDNF in the cortex and a higher pro/mature ratio of BDNF in the hippocampus. We then developed a personalized approach to treating genetically susceptible individuals by overexpressing wildtype BDNF in injured Val66Met mice using an AAV-BDNF virus. This intervention improved cellular, motor, and cognitive behavior outcomes at 21 DPI and increased levels of mature BDNF and phosphorylation of mature BDNF’s receptor trkB. This study lays the groundwork for further investigation into the genetics that play a role in the extent of injury after rmTBI and highlights how personalized therapeutics may be targeted for recovery in susceptible individuals.